The Synaptic Gospel Teaching the Brain to Worship. - Rodkey, Christopher D. (Christopher Demuth) (Lanham : University Press of America, 2012)
In this book, Christopher D. Rodkey asks how the brain worships and responds by engaging ideas from neurological science, philosophy, ritual theory, and religious education. The Synaptic Gospel will prove to be a useful theoretical tool for pastors, religious educators, youth ministers, church music professionals, and seminary students.
The Synaptic Gospel; Table of Contents; Acknowledgements and an Opening Apology; Chapter One Introduction, Problems, and Methodologies; Chapter Two Worshiping Communities as Circles of Empathy; Chapter Three The Neuroscience of Emotion and Feeling; Chapter Four The Neurology of Worship; Chapter Five Worship as Religious Education; Chapter Six An Ecology of Liturgy: Habituating Liturgically with Youth; Selected Bibliography; Index.
Print version record.
Keywords: Empathy -- Religious aspects; Psychology and religion; Psychology, Religious; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Psychology and religion; Empathy -- Religious aspects; Electronic books